2022
DOI: 10.1038/s41598-022-13431-7
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional green synthesized Cu–Al layered double hydroxide (LDH) nanoparticles: anti-cancer and antibacterial activities

Abstract: Doxorubicin (DOX) is a potent anti-cancer agent and there have been attempts in developing nanostructures for its delivery to tumor cells. The nanoparticles promote cytotoxicity of DOX against tumor cells and in turn, they reduce adverse impacts on normal cells. The safety profile of nanostructures is an important topic and recently, the green synthesis of nanoparticles has obtained much attention for the preparation of biocompatible carriers. In the present study, we prepared layered double hydroxide (LDH) na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…[98] Among them, LDH and their nanocomposites have been widely used in the field of tumors therapy due to their excellent properties. [22,99] These applications include traditional chemotherapeutic approaches, emerging phototherapies such as photothermal therapy (PTT) and photodynamic therapy (PDT), gene therapy, immunotherapy, chemodynamic therapy (CDT), and combination therapies, among many others. These nanomaterials show great potential in tumor therapy and provide new avenues for developing more effective therapeutic strategies.…”
Section: Therapymentioning
confidence: 99%
“…[98] Among them, LDH and their nanocomposites have been widely used in the field of tumors therapy due to their excellent properties. [22,99] These applications include traditional chemotherapeutic approaches, emerging phototherapies such as photothermal therapy (PTT) and photodynamic therapy (PDT), gene therapy, immunotherapy, chemodynamic therapy (CDT), and combination therapies, among many others. These nanomaterials show great potential in tumor therapy and provide new avenues for developing more effective therapeutic strategies.…”
Section: Therapymentioning
confidence: 99%
“…Although there are many studies reported the fabrication of LDHs in water as a benign solvent, the procedures were based on using toxic materials such as urea, ethylene glycol, dimethyl sulfoxide, etc. 161,162 . Consequently, several investigations should be conducted to find out alternative and eco-friendly materials.…”
Section: Degradation Of Organic Dyesmentioning
confidence: 99%
“…Several recent studies have analyzed and enhanced the LDH-based delivery of therapeutic molecules [ 5 , 53 ], anti-inflammatory drugs [ 54 , 55 ], anticancer drugs [ 27 , 56 , 57 , 58 , 59 , 60 ], and peptide hormones [ 61 ] by improving the drug-release property of LDHs by modification via intercalation, absorption, and other methods. For example, a publication reported the intercalation of nicotinic acid (NA) in LDH interlayers [ 5 ].…”
Section: Design Of Functional Ldh Nanohybrids For Drug Deliverymentioning
confidence: 99%